Over Criminalization in Panel Legislative Rules as an Obstacle to the Legal Security - Hassan, Mohammed Rashid; Osman, Sirwan (Journal of Legal and Political Studies, 2019)
This research is an attempt by us to illustrate the problem of inflation in penal texts as one of the manifestations of violation of criminal legal security. This is due to the large number of penal legal rules within the penal legislation in general and the special penal laws in particular, the exposure to particulars and the detailed issues contained in the general principles of law, and the transformation of many of these general principles into unnecessary legislative rules. We began this study by presenting the concept of legal security and its components in general to all branches of laws, in order to understand the enlargement of criminal texts as one of the symptoms that impede the achievement of criminal legal security. Then we discussed the causes of the problem of inflation in penal legislation, and then we moved to the applications of the problem of inflation in the penal legislation of Iraq, and then follow these applications look for the effects of inflation in criminal legislation, and finally we concluded this research study of the penal legislation and the special relationship to the phenomenon of inflation penalty.
Keywords: problem of inflation; penal texts; criminal legal security; legal security; general principles of law